1996
DOI: 10.1007/bf01806673
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survivors: Psychosocial concerns and quality of life

Abstract: Breast cancer survivors appear to attain maximum recovery from the physical and psychological trauma of cancer treatment by one year after surgery. A number of aspects of QL and rehabilitation problems worsen after that time. Nevertheless, breast cancer survivors rate their QL more favorably than outpatients with other common medical conditions, and they identify many positive aspects from the cancer experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
301
4
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 460 publications
(342 citation statements)
references
References 24 publications
26
301
4
11
Order By: Relevance
“…Corroborating the results of other studies, (Lasry et al, 1987;Ganz et al, 1995Ganz et al, , 1996Ganz et al, , 1998bLindley et al, 1998;Meyerowitz et al, 1999), both marital status and partner's difficulty understanding were associated with sexual problems in this study. In addition, sexual problems were associated with vaginal dryness, a side effect of breast cancer treatment (the positive association between vaginal dryness and being sexually active is very likely because women tended to become aware of vaginal dryness by engaging in sexual activity).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Corroborating the results of other studies, (Lasry et al, 1987;Ganz et al, 1995Ganz et al, , 1996Ganz et al, , 1998bLindley et al, 1998;Meyerowitz et al, 1999), both marital status and partner's difficulty understanding were associated with sexual problems in this study. In addition, sexual problems were associated with vaginal dryness, a side effect of breast cancer treatment (the positive association between vaginal dryness and being sexually active is very likely because women tended to become aware of vaginal dryness by engaging in sexual activity).…”
Section: Discussionsupporting
confidence: 87%
“…In an earlier analysis of Phase 1 data, Bloom et al (1998) found that women interviewed soon after diagnosis had a better body image than those interviewed at 6-7 months postdiagnosis. This result is consistent for EuroAmerican women and Asian women (Ganz et al, 1996;Ashing-Giwa et al, 2004).…”
Section: Body Image Sexuality and Sexual Problemssupporting
confidence: 81%
“…Ganz and colleagues [20][21][22] have shown that quality-of-life and functional outcome are decreased during and after treatment, but our data suggest a decrement in these parameters before treatment. Significant correlations were observed between reports of poor sleep and the FACT-B instrument, which measures the impact of acknowledging a cancer diagnosis on daily functioning.…”
Section: Discussioncontrasting
confidence: 72%
“…Surviving cancer might also coincide with attitudinal changes. Cancer patients report that the cancer experience changed them in many ways, that it enriched them, deepened the compassion that they felt for others and energized them to look for changes in their environment and the future [33]. These effects of cancer can not be ignored when talking about quality of life issues.…”
Section: Discussionmentioning
confidence: 99%